2019
DOI: 10.1371/journal.ppat.1007903
|View full text |Cite
|
Sign up to set email alerts
|

Stable integrant-specific differences in bimodal HIV-1 expression patterns revealed by high-throughput analysis

Abstract: HIV-1 gene expression is regulated by host and viral factors that interact with viral motifs and is influenced by proviral integration sites. Here, expression variation among integrants was followed for hundreds of individual proviral clones within polyclonal populations throughout successive rounds of virus and cultured cell replication, with limited findings using CD4+ cells from donor blood consistent with observations in immortalized cells. Tracking clonal behavior by proviral “zip codes” indicated that mu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 75 publications
(103 reference statements)
2
19
0
Order By: Relevance
“…1B ). Consistent with previously reported differences in bimodal expression patterns among proviral clones ( 53 ), the results showed that each clonal pool was comprised of both GFP + and GFP − cells, with LTR-active proportions being discernible by GFP + percentages (%GFP + ) that differed among the clones: mostly GFP + cells for some clones (high-%GFP + clones) and distinctly different GFP + percentages for others ( Fig. 1B ).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…1B ). Consistent with previously reported differences in bimodal expression patterns among proviral clones ( 53 ), the results showed that each clonal pool was comprised of both GFP + and GFP − cells, with LTR-active proportions being discernible by GFP + percentages (%GFP + ) that differed among the clones: mostly GFP + cells for some clones (high-%GFP + clones) and distinctly different GFP + percentages for others ( Fig. 1B ).…”
Section: Resultssupporting
confidence: 92%
“…2C are represented in light gray; regions that appear to display darker shading indicate the presence of multiple clones at the same coordinates. We and others have previously reported significant differences among HIV-1-infected cell clones in the amount of virus released per active cell ( 23 , 53 ), and the results here indicated that burst sizes for the integrant clones in the current study ranged over 4 orders of magnitude.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Interestingly, control CD4 T cell cultures in the absence of stimulation had negligible CFR levels at T0 through T14, although infectious particles were revealed when supernatants were passed onto the CD4/MOLT-4 CCR5 virus amplification co-culture system used in TZA. This highlights the need to control for spontaneous HIV-1 reactivation in any experiment on latency reversal, both in vitro [45] and in vivo [46].…”
Section: Discussionmentioning
confidence: 99%